2017
DOI: 10.1155/2017/9205016
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy during Adolescence and Associated Risks: An 8-Year Hospital-Based Cohort Study (2007–2014) in Romania, the Country with the Highest Rate of Teenage Pregnancy in Europe

Abstract: Aim. To determine pregnancy and delivery outcomes among teenagers. Materials and Methods. An 8-year retrospective comparative hospital-based cohort study is analysing singleton pregnancy comorbidities and delivery parameters of a teenage group under the age of 20 compared with a young adult group 20–24 years of age in a university hospital. Results. Teenage is a risk factor for preterm birth <37 weeks (1.21 [1.08–1.35]), foetal growth restriction (1.34 [1.21–1.48]), episiotomy (1.27 [1.21–1.34]), uterine revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
46
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 22 publications
15
46
0
13
Order By: Relevance
“…The risk of cesarean delivery in adolescent pregnancy reduced by 25% than adult pregnancy, which was consistent with the previous found, with aRR (95%CI) varying from 0.49 (0.42-0.59) to 0.79 (0.75-0.89) [1,2,13,16,28,29]. In fact, adolescent women were at the stage of physical growth, with immature reproductive system, and the incidence of cephalopelvic disproportion in adolescent pregnancy was higher than that of adult women [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The risk of cesarean delivery in adolescent pregnancy reduced by 25% than adult pregnancy, which was consistent with the previous found, with aRR (95%CI) varying from 0.49 (0.42-0.59) to 0.79 (0.75-0.89) [1,2,13,16,28,29]. In fact, adolescent women were at the stage of physical growth, with immature reproductive system, and the incidence of cephalopelvic disproportion in adolescent pregnancy was higher than that of adult women [30].…”
Section: Discussionsupporting
confidence: 91%
“…The adverse maternal outcomes of the adolescent pregnant had no difference from those of adult pregnant in our study, such as in PE, placenta previa, placental abruption, postpartum hemorrhage, and some studies were consistent with our findings [13,16,25,26,29]. Some studies found that adolescent pregnancy increased the risk of postpartum hemorrhage [1,16]and PE [1].…”
Section: Discussionsupporting
confidence: 89%
“…Age is an important aspect in the acquisition of hepatitis C virus because it is a factor that gives information about the the most common route of transmission wich differs in children compared to adults, the chances of spontaneous clearance, and possible comorbidities associated that play an important role in progression to cirrhosis and hepatocarcinoma [13]. As the most common route of transmission in children is vertical, it is important to educate mothers about measures that can reduce the risk of transmission during and after birth [14]. In children and adolescents fulminant forms of hepatitis are rare compared to adults.…”
Section: Results and Discussion Agementioning
confidence: 99%
“…Although most mothers were between 18 and 34 years of age, the highest proportion of child deaths in the first year of life (1.2%) occurred among the children of those under 18. This age group presents a higher risk for complications, since younger women are still in the phase of physical and psychological development and, part of them, performing their studies in primary, secondary or even higher education [23,24]. Single, legally separated or widowed women presented a higher risk of death than those married or in a stable union (RR = 1.95; CI95% 1.77-2.15).…”
Section: Discussionmentioning
confidence: 99%